Self Identity of the Main Character of Archie The RedCat's Sri Asih Webtoon: A Literature Study - Prayuda, Vian Ardiansyah; Merawati, Fitri (Journal of Language and Literature Studies, 2025)
This study examines the formation of self-identity in the main character of the Sri Asih Webtoon by Archie the RedCat and Devita Krisant, focusing on three key stages: the real, imaginary, and symbolic. Using Jacques Lacan's social identity theory as the theoretical framework, this research aims to explore how Alana’s identity evolves through these stages. The study employs a qualitative descriptive method, with data collected through library research, reading, listening, and note-taking. The analysis centers on the Webtoon’s narrative, specifically examining the development of Alana's self-identity.The findings reveal that Alana’s self-identity progresses from confusion and self-doubt to complete understanding and acceptance of her role as Sri Asih. In the real stage, Alana lacks self-recognition and awareness of her abilities (Episodes 3, 5, and 18). During the imaginary stage, she begins to associate herself with Sri Asih’s strengths but remains uncertain of her full potential (Episodes 8, 13, and 30). At the symbolic stage, Alana achieves a holistic understanding and acceptance of her identity as Sri Asih (Episodes 14 and 21). This study offers valuable insights into the complex process of self-identity formation, contributing to the broader fields of literary analysis and identity studies. By analyzing Alana’s journey, the study underscores the psychological and narrative mechanisms that shape individual identity in modern storytelling, with implications for understanding character development and identity construction in various media.